Factors associated with arthritis self-efficacy in people living with knee osteoarthritis - Ching, Angela (2019)
Background: People living with knee osteoarthritis (OA) have unrelenting pain and functional limitations and are less likely to self-manage their knee OA through exercise, especially those with activity-related knee pain. Previous research has shown that self-efficacy has a consistent relationship with knee OA symptoms, depression, and physical limitations. Thus, it is important to target the determinants of sub-optimal self-efficacy perceptions, as it could be helpful for people living with knee OA to increase their self-beliefs in successful self-management of arthritis. There is a gap in the literature to investigate the relationship between the different variants of self-efficacy and psychosocial factors, and whether any of these are predictors of arthritis self-efficacy.